Changements d'espace : dilatation (la mer) et réduction (la forêt du Morois) dans l’oeuvre tristanienne - Kiss, Kornélia (Verbum – Analecta Neolatina, 2014)
In this paper, I wish to demonstrate the different psychological effects by means of which nature and space can influence nature and human behavior. I will elaborate on spaces and expanded spaces of the Tristanien myth, influencing and, at the same time, guiding the conduct of the protagonists, especially Tristan, who, throughout his short life, is constantly in close, even: too close relationship with nature, which is a particularly decisive factor concerning his physical andmoral destiny. According to the Bachelardian thought, “man and world exist in a community of dangers. They are dangerous for each other”. Even if the “cohabitation” of the elements of nature and human beings is not always and without negative exception on Earth, it is, however, in continual change. My goal is to show the negative as well as the positive sides of this relationship.